ELECTROCHEMICAL APTASENSOR BASED POLYPYRROLE-IRON OXYHYDROXIDE NANOCOMPOSITE FOR DETECTION OF DIMETHYLPHOSPHONATE (DMMP) - Farah Nabila Diauudin (Tesis, 2022)
This work was carried out in order to build and improve the existing biosensor for detecting DMMP (Dimethyl Methylphosponate).